Cannabis mythology: the process of shaping from experience in Nakhon Si Thammarat, Thailand - Fareeda Jeh-oh; Attanan Tachopisalwong (Cogent Arts & Humanities)
This study analyzes the evolving mythology of cannabis in Thailand, focusing on how shifts in cultural beliefs and institutional narratives influence its transformation from an illicit substance to a medically acknowledged medicine. This study uses Barthes’ theory of myth to analyze how cultural institutions—namely governmental, educational, healthcare, and media organizations—reshape the perception of cannabis to conform to changing ideologies. Historically, these organizations perpetuated the stigmatization of cannabis through anti-drug campaigns and prohibitive legislation. Recent global and local changes have resulted in the redefinition of cannabis within wellness and therapeutic frameworks. This study employs qualitative data derived from 25 interviews with therapeutic cannabis users and healthcare professionals in Nakhon Si Thammarat (NST)to examine the reconstruction of meaning. Semi-structured interviews provided insights into personal experiences, institutional influences, and societal perceptions of cannabis. Research suggests that the perception of cannabis is currently influenced by a combination of governmental regulation and community practices, consistent with Barthes’ concept that myths are malleable entities, perpetually reconfigured by existing power structures and societal demands. This transition highlights the function of cultural institutions in both mythologizing and demythologizing societal symbols.